ANALISIS WAKTU STANDAR DALAM PENENTUAN JUMLAH TENAGA KERJA PADA PRODUKSI CAGE WHEEL DENGAN METODE STOPWATCH TIME STUDY - Dea Ayu Maharani Andris; Handy Febri Satoto (Jurnal Taguchi : Jurnal Ilmiah Teknik dan Manajemen Industri, 2023)
CV. Lancar Jaya is an industrial company in the field of manufacturing spare parts for agricultural equipment, one of which is Cage Wheel spare parts. In the production process, this company has several obstacles, including not having a standard time for workers to complete one unit of spare parts, so that each worker does not have a set target for completing how many units in a day. This causes some production to be unfulfilled, as well as fluctuating demand, where every month the total demand is not fixed. The assembly process is also done manually, so workers in the assembly section are an important factor in having a standard completion time in setting monthly production targets. The purpose of this study is to determine the standard time for workers to complete one Cage Wheel unit, as well as to find the required workforce for each division. The method used to solve the above problems is using the Stopwatch Time Study method. Data processing results obtained standard time on wheel cage size 16 for 20.48 minutes, wheel cage size 14 for 18.25 minutes and wheel size 12 for 17.10 minutes. With a vulnerable workforce of 1-2 people in each division